2011
DOI: 10.3791/3382
|View full text |Cite
|
Sign up to set email alerts
|

Protocols for Vaginal Inoculation and Sample Collection in the Experimental Mouse Model of <em>Candida</em> vaginitis

Abstract: Vulvovaginal candidiasis (VVC), caused by Candida species, is a fungal infection of the lower female genital tract that affects approximately 75% of otherwise healthy women during their reproductive years 18,[32][33][34] . Predisposing factors include antibiotic usage, uncontrolled diabetes and disturbance in reproductive hormone levels due to pregnancy, oral contraceptives or hormone replacement therapies 33,34 . Recurrent VVC (RVVC), defined as three or more episodes per year, affects a separate 5 to 8% of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 42 publications
0
68
0
4
Order By: Relevance
“…Interestingly, adaptive cell-mediated or humoral immunity appears to play no role in protection against infection, although certain epitope-specific antibodies characterized as protective antibodies can be used therapeutically against infection (134,135,(150)(151)(152). Another interesting caveat is that while Th17 responses are critical to neutrophil responses at other anatomical sites (oral, bloodstream), the role for Th17 responses in the vaginal neutrophil response is controversial (139,153). The strongest evidence to date has shown that mice deficient in several cytokines encompassing the Th17 axis showed no change in the C. albicans-in-FIG 6 Rat model of Candida-associated denture stomatitis.…”
Section: Non-cd4mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, adaptive cell-mediated or humoral immunity appears to play no role in protection against infection, although certain epitope-specific antibodies characterized as protective antibodies can be used therapeutically against infection (134,135,(150)(151)(152). Another interesting caveat is that while Th17 responses are critical to neutrophil responses at other anatomical sites (oral, bloodstream), the role for Th17 responses in the vaginal neutrophil response is controversial (139,153). The strongest evidence to date has shown that mice deficient in several cytokines encompassing the Th17 axis showed no change in the C. albicans-in-FIG 6 Rat model of Candida-associated denture stomatitis.…”
Section: Non-cd4mentioning
confidence: 99%
“…(Reprinted from reference 166. ) duced neutrophil response, suggesting little to no role for the Th17 response in VVC (139).…”
Section: Non-cd4mentioning
confidence: 99%
See 1 more Smart Citation
“…On days 2, 6, and 10 after the infection, the vaginal load of C. albicans was evaluated through vaginal lavage with 0.1 mL of PBS, and the fungal count was determined by the CFU assay on sabouraud dextrose agar (SDA). 35 Eight days after the treatment period, the animals were subjected to recurrent control of the infection to further identify and to diagnose the infectious states that may eventually emerge after the previously performed treatment. At day 24, the animals were euthanatized by CO 2 chamber intoxication.…”
Section: Experimental Vvcmentioning
confidence: 99%
“…Currently, rats and mice are considered the most used animal as models to study candidiasis (Carrara et al, 2010;Yano and Fidel, 2011). Fidel et al (1993) established the following steps are necessary to the persistent vaginal infection development, which constitutes fungus penetration, tissue invasion, development and proliferation of this fungus in these animals and the estrogen treatment to induce a pseudo-estrus state.…”
Section: Discussionmentioning
confidence: 99%